2022
DOI: 10.1186/s12891-022-05044-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies aimed at preventing long-term opioid use in trauma and orthopaedic surgery: a scoping review

Abstract: Background Long-term opioid use, which may have significant individual and societal impacts, has been documented in up to 20% of patients after trauma or orthopaedic surgery. The objectives of this scoping review were to systematically map the research on strategies aiming to prevent chronic opioid use in these populations and to identify knowledge gaps in this area. Methods This scoping review is reported according to the Preferred Reporting Items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 159 publications
(633 reference statements)
0
15
0
Order By: Relevance
“…19 On a system level, interventions in hospital guidelines and protocols for opioid prescription have been associated with decreased opioid use in the long run. 20 Our study was notable in that we evaluated opioid use specifically in patients with pelvic fractures which has not previously been investigated in depth. There were several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…19 On a system level, interventions in hospital guidelines and protocols for opioid prescription have been associated with decreased opioid use in the long run. 20 Our study was notable in that we evaluated opioid use specifically in patients with pelvic fractures which has not previously been investigated in depth. There were several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the strategies perceived to be frequently used and most effective are those associated with significant decreases in opioid long-term use following trauma or recommended in several practice guidelines, as shown in a recent scoping review. 32 These include multimodal analgesia, guidelines and protocols, training for clinicians, educational strategies for patients with or without support for opioid tapering, and prescription monitoring systems. Guidelines and education are strategies fostering knowledge, decision processes, awareness of consequences and reinforcement, which are the underpinnings of the capacity and motivation to adopt the desired behavior, 67 including those aimed at alleviating pain and reducing opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Two preventive strategies rated as likely to be highly effective following traumatic injury by our survey respondents—i.e., physical stimulation and establishing communication mechanisms between professionals to optimize the follow-up of patients using opioids—have been studied little to date. 32 Rehabilitation strategies, including physical therapy, have been associated with reduced opioid use in patients with chronic noncancer pain when integrated into multimodal approaches, but studies on their effect as a stand-alone treatment are still limited. 72 Nevertheless, a systematic review of studies, mostly in primary care, showed that interprofessional collaboration was a promising strategy to improve appropriate opioid use and reduce opioid use disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopaedic surgeons should also thoroughly assess current opioid intake before surgery to detect all patients exposed to opioids and take action before surgery, when possible. In this case, patients with pre-exposure to opioids may also benefit from further intervention before surgery 27,53,54 . For a patient who is being considered for reduction or elimination of opioids before surgery, it is essential to maintain communication between pain specialists and orthopaedic surgeons to facilitate a full and safe recovery after surgery.…”
Section: Team Approach: Role-specific Interventionmentioning
confidence: 99%